Action Plan to combat infections due to carbapenem-resistant, Gram-negative pathogens in acute-care hospitals in Greece. Issue 1 (March 2014) - Maltezou, Helena C.; Kontopidou, Flora; Dedoukou, Xanthi; Katerelos, Panagiotis; Gourgoulis, Georgios-Michael; Tsonou, Paraskeui; Maragos, Antonis; Gargalianos, Panagiotis; Gikas, Achilleas; Gogos, Charalambos; Koumis, Ioannis; Lelekis, Moyssis; et al.
Abstract: The prevalence of carbapenem-resistant pathogens (CRPs) has increased worldwide. Given the importance of CRPs for public health and the high rates of carbapenem resistance observed in Greece, the Hellenic Center for Disease Control and Prevention (HCDCP) under the auspices of the Ministry of Health has undertaken initiatives to develop an Action Plan (i) to estimate the burden of CRP infections in acute-care hospitals in Greece and (ii) to implement infection control measures to limit the intrahospital transmission of these organisms. Starting in November 2010, specific infections caused by CRPs were reported to the HCDCP weekly. Results showed that CRP infections constitute a significant public health problem in acute-care hospitals in this country, with a mean incidence of 0.48 per 1000 patient-days and a crude 28-day mortality rate of 34.4%. The second phase of the Action Plan consists of systemic evaluation for adherence to an infection control bundle including enhanced standard infection control practices, separation of carriers and infected patients from non-carriers, and strict implementation of contact precautions. Communication between hospitals and public health authorities has been established to facilitate rapid notification and feedback.